Uji Aktivitas Antikonvulsan Kombinasi Diazepam dan Minyak Pala pada Mencit Jantan Terinduksi Striknin: Uji Aktivitas Antikonvulsan Kombinasi Diazepam dan Minyak Pala pada Mencit Jantan Terinduksi Striknin - Yovita Mercya; Rahmah Asyiah (JURNAL FARMASI DAN MAKANAN, 2025)
Seizures are characterized by sudden, uncontrolled electrical disturbances in the brain that affect behavior, movement, and consciousness. Diazepam, a benzodiazepine, is widely used to manage seizures by enhancing GABA-mediated inhibition. Previous studies suggest that Myristica fragrans (nutmeg) essential oil also has anticonvulsant properties through a similar mechanism. This study aimed to investigate the synergistic anticonvulsant effect of combining diazepam and nutmeg essential oil using a strychnine-induced seizure model in mice. Twenty-four male Mus musculus were divided into four groups: a negative control group, a diazepam group (2 mg/kgBW), a nutmeg oil group (200 mg/kgBW), and a combination group receiving both agents. All groups received 3 mg/kgBW strychnine to induce seizures. The Kruskal-Wallis test showed significant differences in seizure onset and duration among the groups (p = 0.001 and p = 0.000). Further analysis with the Mann-Whitney test showed that the combination group (Group 3) had significantly better outcomes (p = 0.004 and p = 0.003) compared to diazepam alone, with a mean rank of 57.00 vs. 21.00. Mortality in the combination group was also lower (33%) than the other groups (100%). These results indicate a potential synergistic effect between diazepam and nutmeg oil.